Preparation method and application of gold nanocluster composite material based on spiropyrane modification
By coating the spiropyran modified bovine serum albumin on the gold nanoclusters to form a composite material, the non-luminescent state and single luminescent wavelength of spiropyran and gold nanoclusters in the field of anti-counterfeiting in the prior art is solved. The problem of dynamic fluorescence changes and more complex encryption and anti-counterfeiting mode are realized.
Patent Information
- Application Number
- CN202310819362.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-02-07
AI Technical Summary
The existing applications of spiropyran and gold nanoclusters in the field of anti-counterfeiting have problems with non-luminescence state and single luminescence wavelength, which limits their application in the field of advanced encryption and anti-counterfeiting.
Bovine serum albumin is modified by spiropyran, and the modified bovine serum albumin is coated on gold nanoclusters to form a gold nanocluster composite based on spiropyran modification. The composite material exhibits dynamic fluorescence changes through the fluorescence resonance energy transfer effect.
It realizes dynamic fluorescence changes from green to yellow and eventually to orange and red, enhancing the application potential of materials' information storage and anti-counterfeiting, and at the same time, the process is simple, safe and environmentally friendly.
Smart Images

Figure HDA0004323037380000011 
Figure HDA0004323037380000012 
Figure HDA0004323037380000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of luminescent material preparation, and specifically relates to a preparation method and application of a spiropyran-modified gold nanocluster composite material. Background Art
[0002] Spiropyran is a typical molecular light switch with unique photochromic ability. Photochromism refers to the coloring or color change of a photochromic group under light irradiation through reversible isomerization between two chemical structures with different physical and chemical properties, accompanied by a fluorescence switching phenomenon. The closed-ring isomer of spiropyran is referred to as "SP", which is a non-conjugated, colorless, and non-fluorescent structure; while its open-ring isomer (referred to as "MC") is a conjugated, colored, and fluorescent structure. The two structures have significantly different colors and fluorescence properties, and can undergo reversible transformation under the switching of ultraviolet / visible light, thereby showing the characteristics of dynamic luminescence. Therefore, based on the dynamic luminescence characteristics of spiropyran, it is widely used in various fields, especially in the fields of anti-counterfeiting and information encryption. Although spiropyran has the characteristics of dynamic luminescence, the non-luminescent state and single luminescence wavelength in the process of dynamic luminescence of spiropyran affect its application in the field of advanced encryption and anti-counterfeiting that requires more complexity.
[0003] Gold nanoclusters (AuNCs), which consist of a few to dozens of atoms, have an ultra-small size (less than 2nm) close to the Fermi wavelength of electrons. The energy level splitting phenomenon caused by the size effect makes them exhibit stable and excellent fluorescence properties. They are highly promising new luminescent materials and have been widely used in sensing, bioimaging, catalysis and other fields. At the same time, due to their good biocompatibility and stable and adjustable photoluminescent properties, AuNCs have great potential as new luminescent materials for use in information storage and anti-counterfeiting fields.
[0004] Although some studies have attempted to use AuNCs directly as anti-counterfeiting materials, their static fluorescence colors can be replaced by other materials with the same luminescence mode, so the security level of such static anti-counterfeiting modes is low, which limits their further use in the field of advanced anti-counterfeiting. Combining spiropyran units with AuNCs by physical or chemical means can achieve dynamic multicolor fluorescence through time-gated ultraviolet light irradiation. Constructing dynamic luminescent materials based on AuNCs can achieve more complex encrypted anti-counterfeiting modes, which is an important way to expand its application in the field of advanced anti-counterfeiting. Summary of the invention
[0005] In view of the shortcomings of spiropyran and AuNCs in the prior art in the field of anti-counterfeiting, the purpose of the present invention is to provide a method for preparing a spiropyran-modified gold nanocluster composite material. The preparation method of the present invention is to modify bovine serum albumin using spiropyran, and then coat the gold nanocluster with the spiropyran-modified bovine serum albumin to obtain a spiropyran-modified gold nanocluster composite material. Based on the fluorescence resonance energy transfer effect between the open-ring isomer MC of spiropyran and AuNCs, the composite material exhibits dynamic fluorescence changes. The preparation method is simple in process and has good repeatability, is safe and environmentally friendly, and does not require the use of complex instruments and equipment and operations. The spiropyran-modified gold nanocluster composite material synthesized by the present invention not only has dynamic fluorescence properties, but also has photochromic properties due to the presence of spiropyran, and has great application potential in the fields of information storage and anti-counterfeiting.
[0006] The specific preparation method of the present invention is as follows:
[0007] The activated carboxyl spiropyran and bovine serum albumin are stirred and reacted for 2-4 hours to obtain spiropyran-modified bovine serum albumin; the spiropyran-modified bovine serum albumin and gold nanoclusters are then stirred and mixed evenly, and anhydrous ethanol is added dropwise; after the solution becomes turbid after the addition of ethanol, glutaraldehyde is added and reacted for 8-24 hours to obtain a composite material based on spiropyran-modified gold nanoclusters.
[0008] Furthermore, the activated carboxyl spiropyran is prepared by the following process: carboxyl spiropyran, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are uniformly mixed and then allowed to react to obtain the activated carboxyl spiropyran.
[0009] Furthermore, the usage ratio of carboxyspiropyran, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide is 4 μmol:3.5-4.5 mg:3.5-4.5 mg.
[0010] Furthermore, the activation time of the carboxyspiropyran is 12-24 hours.
[0011] Furthermore, the molar ratio of spiropyran to bovine serum albumin is 1-2:1.
[0012] Furthermore, the molar ratio of spiropyran to gold nanoclusters is 1:1-1.8.
[0013] Furthermore, the volume ratio of bovine serum albumin to anhydrous ethanol is 1:1.5-2.
[0014] Furthermore, the molar ratio of bovine serum albumin to glutaraldehyde is 1:46-58.
[0015] Beneficial effects of the present invention
[0016] The present invention uses bovine serum albumin as a bridge, that is, by coating AuNCs with spiropyran-modified bovine serum albumin, to successfully achieve efficient composite between spiropyran and AuNCs with large solubility differences, and prepares a spiropyran-modified gold nanocluster composite material.
[0017] Furthermore, since the absorption spectrum of the ring-opening isomer MC of spiropyran is highly overlapped with the emission spectrum of the AuNCs selected in the present invention, that is, efficient fluorescence resonance energy transfer can occur between spiropyran and AuNCs, the gold nanocluster composite material modified by spiropyran in the present invention has unique dynamic fluorescence properties. Under the irradiation of ultraviolet light, the gold nanocluster composite material modified by spiropyran exhibits dynamic fluorescence changes from green to yellow and finally to orange-red, and this process can be reversibly transformed by irradiation of visible light. Moreover, due to the presence of spiropyran, the composite material also has photochromic properties. Based on the above properties, the gold nanocluster composite material modified by spiropyran has great application potential in the fields of anti-counterfeiting and information storage.
[0018] Furthermore, the present invention uses bovine serum albumin as a carrier to solve the problem of poor water solubility of spiropyran, so that the prepared spiropyran-modified gold nanocluster composite material has good water solubility. At the same time, the preparation process of the present invention is simple and reproducible, safe and environmentally friendly, does not require the use of complex instruments and equipment and operations, and is very friendly to material manufacturers and users. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram of the preparation of the spiropyran-modified gold nanocluster composite material of the present invention;
[0020] Figure 2 Figure 1 is a transmission electron microscope image and element distribution of the AuNCs@BSA-SP composite material prepared in Example 1 of the present invention, wherein Figure (a) is a single transmission electron microscope image, Figure (b) is an energy spectrum scanning area, and Figures (c), (d), (e), (f) and (g) are distribution diagrams of C, N, O, Au and S elements, respectively;
[0021] Figure 3 The figure is a dynamic fluorescence change effect diagram of the AuNCs@BSA-SP composite material solution prepared in Example 1 of the present invention under ultraviolet light irradiation, wherein Figure (a) is a photograph of the dynamic fluorescence change of the composite material solution during ultraviolet light irradiation, and Figure (b) is the chromaticity coordinate change of the fluorescence color of the composite material solution before and after ultraviolet light irradiation;
[0022] Figure 4is a fluorescence spectrum of the AuNCs@BSA-SP composite material solution prepared in Example 1 of the present invention under ultraviolet light irradiation for different time periods;
[0023] Figure 5 This is the application of the AuNCs@BSA-SP / PVA anti-counterfeiting film prepared in Example 2 of the present invention in the fields of information storage and advanced anti-counterfeiting, wherein Figure (a) shows the application of the anti-counterfeiting film in the field of information storage, and Figure (b) shows the application of the anti-counterfeiting film in the field of advanced anti-counterfeiting. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below by way of examples, but the protection scope of the present invention is not limited to the contents described above.
[0025] Embodiment 1:
[0026] (1) Preparation of activated carboxyl spiropyran: Carboxyl spiropyran (SPCOOH) was prepared using hydroxy spiropyran (1-(2-hydroxyethyl)-3,3-dimethylindoline-6'-nitrobenzospiropyran, SPOH) as the raw material. The specific preparation steps are as follows: Linfeng Chen, Wenqian Wang, Bin Su, et al. A Light-Responsive Release Platform by Controlling the Wetting Behavior of Hydrophobic Surface [J]. ACS Nano, 2014, 8(1), 744-751. 4 mg 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and 4 mg N-hydroxysuccinimide (NHS) were added to SPCOOH (20 mM, 200 μL). The above solution was stirred thoroughly to ensure that EDC and NHS were completely dissolved, and then allowed to react for 24 h to obtain activated SPCOOH. The prepared sample-activated SPCOOH was stored at 4°C for future use.
[0027] (2) Preparation of spiropyran-modified bovine serum albumin: Activated SPCOOH (20 mM, 27.6 μL) was added to bovine serum albumin (40 mg / mL, 0.5 mL) under stirring at 1000 rpm, and stirred for 2 h to obtain spiropyran-modified bovine serum albumin (BSA-SP). The prepared BSA-SP sample was stored at 4°C for future use.
[0028] (3) Preparation of spiropyran-modified gold nanocluster composite materials: Gold nanoclusters (Arg / ATT-AuNCs) with arginine / 6-aza-2-thiothymine as ligands were pre-synthesized. For the specific preparation steps, refer to Hao-Hua Deng, Xiao-Qiong Shi, Fei-Fei Wang, et al. Fabrication of Water-Soluble, Green-Emitting Gold Nanoclusters with a 65% Photoluminescence Quantum Yield via Host-Guest Recognition [J]. Chemistry of Materials, 2017, 29(3), 1362-1369. Arg / ATT-AuNCs (12.5 mM, 45 μL) was added to the above 0.5 mL BSA-SP and stirred vigorously at room temperature for 30 min. Then 0.875 mL of anhydrous ethanol was added dropwise. After the solution became turbid, glutaraldehyde (8%, 32 μL) was added and reacted for 12 h to obtain a spiropyran-modified gold nanocluster composite material (AuNCs@BSA-SP).
[0029] Embodiment 2:
[0030] (1) Preparation of activated SPCOOH: SPCOOH was prepared using SPOH as the raw material. The specific preparation steps refer to: Linfeng Chen, Wenqian Wang, Bin Su, et al. A Light-Responsive Release Platform by Controlling the Wetting Behavior of Hydrophobic Surface [J]. ACS Nano, 2014, 8 (1), 744-751. 4 mg EDC and 4 mg NHS were added to SPCOOH (20 mM, 200 μL). The above solution was stirred thoroughly to ensure that EDC and NHS were completely dissolved, and then allowed to react for 24 hours to obtain activated SPCOOH. The prepared sample activated SPCOOH was stored at 4°C for future use.
[0031] (2) Preparation of BSA-SP: SPCOOH (20 mM, 27.6 μL) was added to bovine serum albumin (40 mg / mL, 0.5 mL) under stirring at 1000 rpm, and stirred for 2 h to obtain BSA-SP. The prepared BSA-SP sample was stored at 4°C for future use.
[0032] (3) Preparation of AuNCs@BSA-SP: Arg / ATT-AuNCs with arginine / 6-aza-2-thiothymine as ligands were pre-synthesized. For the specific preparation steps, refer to Hao-Hua Deng, Xiao-Qiong Shi, Fei-Fei Wang, et al. Fabrication of Water-Soluble, Green-Emitting Gold Nanoclusters with a 65% Photoluminescence Quantum Yield via Host-Guest Recognition [J]. Chemistry of Materials, 2017, 29(3), 1362-1369. Arg / ATT-AuNCs (12.5 mM, 80 μL) was added to the above 0.5 mL BSA-SP and stirred vigorously at room temperature for 30 min. Then 0.875 mL of anhydrous ethanol was added dropwise. After the solution became turbid, glutaraldehyde (8%, 40 μL) was added and reacted for 15 h to obtain AuNCs@BSA-SP.
[0033] (4) Preparation of anti-counterfeiting film based on AuNCs@BSA-SP: Add 25 μL of glycerol and 1 mL of the above-mentioned AuNCs@BSA-SP to the polyvinyl alcohol solution (10%, 2.5 mL). After stirring for 6 h, pour the above-mentioned mixed solution on the substrate and dry it naturally at room temperature to obtain the anti-counterfeiting film based on AuNCs@BSA-SP (AuNCs@BSA-SP / PVA anti-counterfeiting film).
[0034] Embodiment 3:
[0035] (1) Preparation of activated SPCOOH: SPCOOH was prepared using SPOH as the raw material. The specific preparation steps refer to: Linfeng Chen, Wenqian Wang, Bin Su, et al. A Light-Responsive Release Platform by Controlling the Wetting Behavior of Hydrophobic Surface [J]. ACS Nano, 2014, 8 (1), 744-751. 4 mg EDC and 4 mg NHS were added to SPCOOH (20 mM, 200 μL). The above solution was stirred thoroughly to ensure that EDC and NHS were completely dissolved, and then allowed to react for 24 hours to obtain activated SPCOOH. The prepared sample activated SPCOOH was stored at 4°C for future use.
[0036] (2) Preparation of BSA-SP: SPCOOH (20 mM, 41.4 μL) was added to bovine serum albumin (40 mg / mL, 0.5 mL) under stirring at 1000 rpm, and stirred for 3 h to obtain BSA-SP. The prepared BSA-SP sample was stored at 4°C for future use.
[0037] (3) Preparation of AuNCs@BSA-SP: Arg / ATT-AuNCs with arginine / 6-aza-2-thiothymine as ligands were pre-synthesized. For the specific preparation steps, refer to Hao-Hua Deng, Xiao-Qiong Shi, Fei-Fei Wang, et al. Fabrication of Water-Soluble, Green-Emitting Gold Nanoclusters with a 65% Photoluminescence Quantum Yield via Host-Guest Recognition [J]. Chemistry of Materials, 2017, 29(3), 1362-1369. Arg / ATT-AuNCs (12.5 mM, 68 μL) was added to the above 0.5 mL BSA-SP and stirred vigorously at room temperature for 30 min. Then 1 mL of anhydrous ethanol was added dropwise. After the solution became turbid, glutaraldehyde (8%, 32 μL) was added and reacted for 12 h to obtain AuNCs@BSA-SP.
[0038] Embodiment 4:
[0039] (1) Preparation of activated SPCOOH: SPCOOH was prepared using SPOH as the raw material. The specific preparation steps refer to: Linfeng Chen, Wenqian Wang, Bin Su, et al. A Light-Responsive Release Platform by Controlling the Wetting Behavior of Hydrophobic Surface [J]. ACS Nano, 2014, 8 (1), 744-751. 4 mg EDC and 4 mg NHS were added to SPCOOH (20 mM, 200 μL). The above solution was stirred thoroughly to ensure that EDC and NHS were completely dissolved, and then allowed to react for 24 hours to obtain activated SPCOOH. The prepared sample activated SPCOOH was stored at 4°C for future use.
[0040] (2) Preparation of BSA-SP: SPCOOH (20 mM, 55.2 μL) was added to bovine serum albumin (40 mg / mL, 0.5 mL) under stirring at 1000 rpm, and stirred for 4 h to obtain BSA-SP. The prepared BSA-SP sample was stored at 4°C for future use.
[0041] (3) Preparation of AuNCs@BSA-SP: Arg / ATT-AuNCs with arginine / 6-aza-2-thiothymine as ligands were pre-synthesized. For the specific preparation steps, refer to Hao-Hua Deng, Xiao-Qiong Shi, Fei-Fei Wang, et al. Fabrication of Water-Soluble, Green-Emitting Gold Nanoclusters with a 65% Photoluminescence Quantum Yield via Host-Guest Recognition [J]. Chemistry of Materials, 2017, 29(3), 1362-1369. Arg / ATT-AuNCs (12.5 mM, 90 μL) was added to the above 0.5 mL BSA-SP and stirred vigorously at room temperature for 30 min. Then 1 mL of anhydrous ethanol was added dropwise. After the solution became turbid, glutaraldehyde (8%, 32 μL) was added and reacted for 12 h to obtain AuNCs@BSA-SP.
[0042] Embodiment 5:
[0043] (1) Preparation of activated SPCOOH: SPCOOH was prepared using SPOH as the raw material. The specific preparation steps refer to: Linfeng Chen, Wenqian Wang, Bin Su, et al. A Light-Responsive Release Platform by Controlling the Wetting Behavior of Hydrophobic Surface [J]. ACS Nano, 2014, 8 (1), 744-751. 4 mg EDC and 4 mg NHS were added to SPCOOH (20 mM, 200 μL). The above solution was stirred thoroughly to ensure that EDC and NHS were completely dissolved, and then allowed to react for 24 hours to obtain activated SPCOOH. The prepared sample activated SPCOOH was stored at 4°C for future use.
[0044] (2) Preparation of BSA-SP: SPCOOH (20 mM, 34.5 μL) was added to bovine serum albumin (62.5 mg / mL, 0.4 mL) under stirring at 1000 rpm, and stirred for 2.5 h to obtain BSA-SP. The prepared BSA-SP sample was stored at 4°C for future use.
[0045] (3) Preparation of AuNCs@BSA-SP: Arg / ATT-AuNCs with arginine / 6-aza-2-thiothymine as ligands were pre-synthesized. For the specific preparation steps, refer to Hao-Hua Deng, Xiao-Qiong Shi, Fei-Fei Wang, et al. Fabrication of Water-Soluble, Green-Emitting Gold Nanoclusters with a 65% Photoluminescence Quantum Yield via Host-Guest Recognition [J]. Chemistry of Materials, 2017, 29(3), 1362-1369. Arg / ATT-AuNCs (12.5 mM, 57 μL) was added to the above 0.4 mL BSA-SP and stirred vigorously at room temperature for 30 min. Then 0.6 mL of anhydrous ethanol was added dropwise. After the solution became turbid, glutaraldehyde (8%, 40 μL) was added and reacted for 15 h to obtain AuNCs@BSA-SP.
[0046] Embodiment 6:
[0047] (1) Preparation of activated SPCOOH: SPCOOH was prepared using SPOH as the raw material. The specific preparation steps refer to: Linfeng Chen, Wenqian Wang, Bin Su, et al. A Light-Responsive Release Platform by Controlling the Wetting Behavior of Hydrophobic Surface [J]. ACS Nano, 2014, 8 (1), 744-751. 4 mg EDC and 4 mg NHS were added to SPCOOH (20 mM, 200 μL). The above solution was stirred thoroughly to ensure that EDC and NHS were completely dissolved, and then allowed to react for 24 hours to obtain activated SPCOOH. The prepared sample activated SPCOOH was stored at 4°C for future use.
[0048] (2) Preparation of BSA-SP: SPCOOH (20 mM, 34.5 μL) was added to bovine serum albumin (62.5 mg / mL, 0.4 mL) under stirring at 1000 rpm, and stirred for 2.5 h to obtain BSA-SP. The prepared BSA-SP sample was stored at 4°C for future use.
[0049] (3) Preparation of AuNCs@BSA-SP: Arg / ATT-AuNCs with arginine / 6-aza-2-thiothymine as ligands were pre-synthesized. For the specific preparation steps, refer to Hao-Hua Deng, Xiao-Qiong Shi, Fei-Fei Wang, et al. Fabrication of Water-Soluble, Green-Emitting Gold Nanoclusters with a 65% Photoluminescence Quantum Yield via Host-Guest Recognition [J]. Chemistry of Materials, 2017, 29(3), 1362-1369. Arg / ATT-AuNCs (12.5 mM, 100 μL) was added to the above 0.4 mL BSA-SP and stirred vigorously at room temperature for 30 min. Then 0.8 mL of anhydrous ethanol was added dropwise. After the solution became turbid, glutaraldehyde (8%, 50 μL) was added and reacted for 19 h to obtain AuNCs@BSA-SP.
[0050] (4) Preparation of AuNCs@BSA-SP / PVA anti-counterfeiting film: 25 μL of glycerol and 1 mL of the above-mentioned AuNCs@BSA-SP were added to the polyvinyl alcohol solution (10%, 2.5 mL). After stirring for 6 h, the mixed solution was poured on the substrate and naturally dried at room temperature to obtain the AuNCs@BSA-SP / PVA anti-counterfeiting film.
[0051] Embodiment 7:
[0052] (1) Preparation of activated SPCOOH: SPCOOH was prepared using SPOH as the raw material. The specific preparation steps refer to: Linfeng Chen, Wenqian Wang, Bin Su, et al. A Light-Responsive Release Platform by Controlling the Wetting Behavior of Hydrophobic Surface [J]. ACS Nano, 2014, 8 (1), 744-751. 4 mg EDC and 4 mg NHS were added to SPCOOH (20 mM, 200 μL). The above solution was stirred thoroughly to ensure that EDC and NHS were completely dissolved, and then allowed to react for 24 hours to obtain activated SPCOOH. The prepared sample activated SPCOOH was stored at 4°C for future use.
[0053] (2) Preparation of BSA-SP: SPCOOH (20 mM, 51.8 μL) was added to bovine serum albumin (62.5 mg / mL, 0.4 mL) under stirring at 1000 rpm, and stirred for 3.5 h to obtain BSA-SP. The prepared BSA-SP sample was stored at 4°C for future use.
[0054] (3) Preparation of AuNCs@BSA-SP: Arg / ATT-AuNCs with arginine / 6-aza-2-thiothymine as ligands were pre-synthesized. For the specific preparation steps, refer to Hao-Hua Deng, Xiao-Qiong Shi, Fei-Fei Wang, et al. Fabrication of Water-Soluble, Green-Emitting Gold Nanoclusters with a 65% Photoluminescence Quantum Yield via Host-Guest Recognition [J]. Chemistry of Materials, 2017, 29(3), 1362-1369. Arg / ATT-AuNCs (12.5 mM, 86 μL) was added to the above 0.4 mL BSA-SP and stirred vigorously at room temperature for 30 min. Then 0.7 mL of anhydrous ethanol was added dropwise. After the solution became turbid, glutaraldehyde (8%, 60 μL) was added and reacted for 22 h to obtain AuNCs@BSA-SP.
[0055] Embodiment 8:
[0056] (1) Preparation of activated SPCOOH: SPCOOH was prepared using SPOH as the raw material. The specific preparation steps refer to: Linfeng Chen, Wenqian Wang, Bin Su, et al. A Light-Responsive Release Platform by Controlling the Wetting Behavior of Hydrophobic Surface [J]. ACS Nano, 2014, 8 (1), 744-751. 4 mg EDC and 4 mg NHS were added to SPCOOH (20 mM, 200 μL). The above solution was stirred thoroughly to ensure that EDC and NHS were completely dissolved, and then allowed to react for 24 hours to obtain activated SPCOOH. The prepared sample activated SPCOOH was stored at 4°C for future use.
[0057] (2) Preparation of BSA-SP: SPCOOH (20 mM, 69 μL) was added to bovine serum albumin (62.5 mg / mL, 0.4 mL) under stirring at 1000 rpm, and stirred for 4 h to obtain BSA-SP. The prepared BSA-SP sample was stored at 4°C for future use.
[0058] (3) Preparation of AuNCs@BSA-SP: Arg / ATT-AuNCs with arginine / 6-aza-2-thiothymine as ligands were pre-synthesized. For the specific preparation steps, refer to Hao-Hua Deng, Xiao-Qiong Shi, Fei-Fei Wang, et al. Fabrication of Water-Soluble, Green-Emitting Gold Nanoclusters with a 65% Photoluminescence Quantum Yield via Host-Guest Recognition [J]. Chemistry of Materials, 2017, 29(3), 1362-1369. Arg / ATT-AuNCs (12.5 mM, 115 μL) was added to the above 0.4 mL BSA-SP and stirred vigorously at room temperature for 30 min. Then 0.75 mL of anhydrous ethanol was added dropwise. After the solution became turbid, glutaraldehyde (8%, 80 μL) was added and reacted for 24 h to obtain AuNCs@BSA-SP.
[0059] The AuNCs@BSA-SP composite material prepared in Example 1 was analyzed by transmission electron microscopy. Figure 2 As shown, Figure 2 (a) is the transmission electron microscopy image of AuNCs@BSA-SP. Figure 2 (b) is the energy spectrum scanning area of AuNCs@BSA-SP. Figure 2 (c), (d), (e), (f), and (g) are the distribution diagrams of C, N, O, Au, and S elements, respectively. It can be seen from the figure that AuNCs@BSA-SP is a regular sphere with a size between 200 and 300 nm. The element distribution shows that C, N, O, Au, and S elements are evenly distributed in the sphere, proving that AuNCs are successfully coated with spiropyran-modified bovine serum albumin.
[0060] Figure 3 The dynamic fluorescence change effect of the AuNCs@BSA-SP composite material solution prepared in Example 1 under ultraviolet light irradiation is shown, wherein Figure 3(a) is a physical picture of the dynamic change of the fluorescence of the composite material aqueous solution under ultraviolet light irradiation as time increases. It can be seen that when the ultraviolet light is first irradiated, the solution emits bright green fluorescence, and when the time is extended to 3s, the fluorescence turns yellow. As the irradiation time is further extended, the fluorescence of the solution eventually turns orange-red; Figure 3 (b) shows the change in the chromaticity coordinates of the fluorescence of the solution before and after ultraviolet light irradiation. The coordinates before and after irradiation are (0.32, 0.64) and (0.57, 0.42), corresponding to green and orange-red.
[0061] In order to further explore the dynamic fluorescence changes of AuNCs@BSA-SP composite materials, we tested the fluorescence spectra of the AuNCs@BSA-SP composite material solution prepared in Example 1 under UV irradiation for different times. The results are as follows: Figure 4 As shown. It can be seen that under ultraviolet light, the composite material solution exhibits two fluorescence peaks, of which the peak around 530nm is AuNCs, and the peak around 630nm is spiropyran. As the ultraviolet light irradiation time increases, the fluorescence peak intensity of AuNCs gradually decreases, while the fluorescence peak intensity of spiropyran gradually increases, which corresponds to the fluorescence color of the material gradually changing from green to orange-red.
[0062] Figure 5 The AuNCs@BSA-SP / PVA anti-counterfeiting film prepared in Example 2 is applied in the fields of information storage and advanced anti-counterfeiting, wherein Figure 5 (a) shows the application of the anti-counterfeiting film in the field of information storage. Due to the presence of spiropyran, the anti-counterfeiting film has a photochromic property. Different information can be stored on the anti-counterfeiting film using ultraviolet light and different masks, and the information can be erased with visible light, so it can be reused; Figure 5 (b) is the application of the anti-counterfeiting film in the field of advanced anti-counterfeiting. First, information is loaded on the anti-counterfeiting film using ultraviolet light and a mask. After removing the mask, a clear pattern of the emblem of the Northwest University of Technology can be seen on the film. Then, ultraviolet light is used for irradiation to realize anti-counterfeiting detection of the pattern. In the first stage, due to the coverage of the mask, the unirradiated part of the film shows dynamic fluorescence changes during the irradiation process in the second stage. Finally, the entire film turns into orange-red fluorescence, and the loaded information is erased after anti-counterfeiting authentication and reading. The anti-counterfeiting film integrates information storage, anti-counterfeiting, and erasure, and can be applied to advanced anti-counterfeiting fields with complex requirements.
[0063] The above disclosure is only a preferred embodiment of the present invention, but in fact the embodiment of the present invention is not limited thereto. Obviously, other technicians in the field can make various changes and modifications to the present invention to achieve the same or similar effects. Therefore, the above content is only to illustrate the technical idea of the present invention, and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution according to the technical idea proposed by the present invention fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a spiropyran-modified gold nanocluster composite material, characterized in that: The following steps are involved: The activated carboxyl spiropyran and bovine serum albumin solution are stirred and reacted for 2-4 hours to obtain spiropyran-modified bovine serum albumin; the spiropyran-modified bovine serum albumin and the gold nanocluster solution are then stirred and mixed evenly, and anhydrous ethanol is added dropwise; after the solution becomes turbid after the addition of ethanol, glutaraldehyde is added and reacted for 8-24 hours to obtain a spiropyran-modified gold nanocluster composite material.
2. The method for preparing the spiropyran-modified gold nanocluster composite material according to claim 1, characterized in that: The activated carboxyl spiropyran is prepared by the following process: carboxyl spiropyran, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide are uniformly mixed and then allowed to stand for reaction to obtain the activated carboxyl spiropyran.
3. The method for preparing the spiropyran-modified gold nanocluster composite material according to claim 2, characterized in that: The usage ratio of carboxyspiropyran, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide is 4 μmol:3.5-4.5 mg:3.5-4.5 mg.
4. The method for preparing the spiropyran-modified gold nanocluster composite material according to claim 2, characterized in that: The activation time of carboxyspiropyran is 12-24h.
5. The method for preparing the spiropyran-modified gold nanocluster composite material according to claim 1, characterized in that: The molar ratio of spiropyran to bovine serum albumin is 1-2:
1.
6. The method for preparing the spiropyran-modified gold nanocluster composite material according to claim 1, characterized in that: The molar ratio of spiropyran to gold nanoclusters is 1:1-1.
8.
7. The method for preparing the spiropyran-modified gold nanocluster composite material according to claim 1, characterized in that: The volume ratio of bovine serum albumin to anhydrous ethanol is 1:1.5-2.
8. The method for preparing the spiropyran-modified gold nanocluster composite material according to claim 1, characterized in that: The molar ratio of bovine serum albumin to glutaraldehyde is 1:46-58.
9. Application of spiropyran-modified gold nanocluster composites in information storage and anti-counterfeiting fields.